PENGARUH PENDIDIKAN TERHADAP KINERJA ASN DI INSPEKTORAT KABUPATEN HALMAHERA UTARA - NAGARA, FRIDORIS; PANGKEY, MASJE Silija; POMBENGI, JERICHO DANGA (JURNAL ADMINISTRASI PUBLIK, 2018)
The method of research that writer use in this research is quantitative research method, that is researchmethod based on philosophy of positivism, which is used for research in certain population or sample. Thesampling technique used is the saturated sample technique from the research in Inspectorate of NorthHalmahera District from 31 ASN. Data analysis techniques used are simple linear regression analysis andsimple correlation analysis.Based on the results of analysis using product moment correlation of people obtained correlation coefficient(r) = 0.343 while the coefficient of determination (r2) = 0.34. These results show that the coefficient ofdetermination is 34%. With this result, it can be explained that ASN performance improvement is determinedby education by 34% while 65% is determined by other factors. Based on the results of the above research,the hypothesis in the post can be accepted that there is a level of relevance and determination between ASNperformance educations in North Halmahera district inspectorate. Based on the significant test resultsobtained t = 2.280 at significant level (Î±) = 0.05 with degrees of freedom (df) = n - 2 = 29, then table = 2.045.From the data obtained that t arithmetic greater than ttable where t arithmetic 2,280> 2.045. Then H1 isaccepted and HO is rejected. This proves that there is a positive influence between Education onPerformance Asn in Kab. North HalmaheraBased on the results of the study, it can be concluded that education has an influence on ASN performance.But in the category of calculation of interpretation of education fall into the weak category. So the betterthe ASN education, the better the performance will be, so it should improve the program "education bothformal, informal, non formal education, in the process of achieving performance results.Keywords: Education, Performance of Civil State Apparatus,